Investigation on the mechanical properties of Bacillus subtilis self-healing concrete - Yuanyuan Tie; Yongcheng Ji; Hongzhao Zhang; Bingyan Jing; Xinya Zeng; Peili Yang (Heliyon, 2024)
In the process of research and development of self-healing concrete, it is observed that there are three main factors controlling the self-healing effect of concrete: first, the bacteria with repair ability and strong vitality; Second, the carrying capacity of the carrier and the matching degree with concrete; The third is the concentration of bacteria. This paper focuses on the mechanical properties of Bacillus subtilis self-healing concrete with sisal fiber, PVA, and expanded perlite as the carrier. To better study the mechanical properties of self-healing concrete caused by the carrier, the experiment adopts the design parameters of C30 concrete and conducts experiments on compressive resistance, flexural resistance, freeze-thaw cycle, and sulfate corrosion resistance to analyze the influence of different carriers on the mechanical properties of self-healing concrete, and obtains the best carrier. The concentration gradients of three groups of bacterial solution were set as 2od, 2.5od, and 3od, respectively, for comparison to avoid the influence of bacterial concentration. It compared the impact of bacterial solution concentrations on the specimen's mechanical properties, and the effect of carriers was also analyzed. The experimental results show that the mechanical properties of the specimen using 2.5od bacterial liquid concentration with PVA as the carrier have peaked. With the increase in bacterial solution concentration, the specimens' comprehensive mechanical properties increased first and then decreased. The compression resistance of the specimen with PVA is higher than that of the specimen with sisal fiber and expanded perlite. At the same time, the frost resistance and corrosion resistance of the PVA carrier specimen is also higher than that of the specimen with sisal fiber and expanded perlite carrier.